Burn Serum Increases Staphylococcus aureus Biofilm Formation via Oxidative Stress - Yin, Supeng; Jiang, Bei; Huang, Guangtao; Gong, Yali; You, Bo; Yang, Zichen; Chen, Yu; Chen, Jing; Yuan, Zhiqiang; Li, Ming; Hu, Fuquan; Zhao, Yan; et al. (Frontiers in Microbiology, 2017)
Staphylococcus aureus is a common pathogen isolated from burn patients that can form biofilms on burn wounds and implanted deep vein catheters, which often leads to refractory infections or even biofilm-related sepsis. As biofilm formation is usually regulated by environmental conditions, we hypothesized that serum composition may be altered after burn injury, potentially affecting the ability of infecting bacteria to form biofilms. As predicted, we observed that serum from burn-injured rats increases biofilm formation by Staphylococcus aureus and also induces bacterial aggregation and adherence to human fibronectin and fibrinogen. Analysis of potential regulatory factors revealed that exposure to burn serum decreases expression of the quorum-sensing agr system and increases mRNA levels of some biofilm inducers such as sarA and icaA. In addition, we also observed that burn serum imposes oxidative stress and increases expression of key oxidoreductase genes (sodA, sodM, katA, and ahpC) in S. aureus. Importantly, the ability of burn serum to enhance biofilm formation and bacterial cell aggregation can be abrogated by treatment with an antioxidant. Taken together, these findings indicate that burn serum increases S. aureus biofilm formation via elevated oxidative stress, and may lead to novel strategies to control biofilm formation and infection in burn patients.